PENGARUH DISTRIBUTOR, SUPLIER DAN STAFF INTERNAL TERHADAP KINERJA PEMASARAN UKM DI KOTA BANJARMASIN DAN BANJARBARU - Ni Nyoman Suarniki; Nova Abriano (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, The purpose of this research was to determine the variable distributor, supplier and internal staff have significant effect simultaneously on the marketing performance of SMEs in the city of Banjarmasin and Banjarbaru as well as to determine which of the variables distributors, suppliers and internal staff who have a dominant influence partially on the performance of marketing SMEs in Banjarmasin and Banjarbaru. The research population was all SMEs (small and micro enterprises) in the city of Banjarmasin and Banjarbaru. The collected data will be analyzed qualitatively and quantitatively. For quantitative analysis used Regression. Calculations, the F Count equal to 34.352, while the F-table with α = 5%, with DF1 (number of variable-1)= 4 and DF2 (nk-1) or (110-3-1) = 106 (n is the amount of data and k is the number of independent variables), the obtained value of F-table = 2,401. Can be obtained F count larger than F table (34.352 > 2.401), thus it can be concluded that the variable Distributors, Suppliers and Internal Staff have significant effect simultaneously on the performance of SMEs. Partial test results, then the variable Leads (X2) has the most dominant influence partially on the performance of SMEs. This is evidenced by looking at the biggest variable t Leads (X2) that is equal to 5.567. Then the research hypothesis which says that the variable Supplier has the most dominant influence partially on the performance of SMEs is not proven true.